The Methionine 549 and Leucine 552 Residues of Friedelin Synthase from Maytenus ilicifolia Are Important for Substrate Binding Specificity - Bruna F. Mazzeu; Tatiana M. Souza-Moreira; Andrew A. Oliveira; Melissa Remlinger; Lidiane G. Felippe; Sandro R. Valentini; Rafael V. C. Guido; Cleslei F. Zanelli; Maysa Furlan (Molecules, 2021)
Friedelin, a pentacyclic triterpene found in the leaves of the Celastraceae species, demonstrates numerous biological activities and is a precursor of quinonemethide triterpenes, which are promising antitumoral agents. Friedelin is biosynthesized from the cyclization of 2,3-oxidosqualene, involving a series of rearrangements to form a ketone by deprotonation of the hydroxylated intermediate, without the aid of an oxidoreductase enzyme. Mutagenesis studies among oxidosqualene cyclases (OSCs) have demonstrated the influence of amino acid residues on rearrangements during substrate cyclization: loss of catalytic activity, stabilization, rearrangement control or specificity changing. In the present study, friedelin synthase from Maytenus ilicifolia (Celastraceae) was expressed heterologously in Saccharomyces cerevisiae. Site-directed mutagenesis studies were performed by replacing phenylalanine with tryptophan at position 473 (Phe473Trp), methionine with serine at position 549 (Met549Ser) and leucine with phenylalanine at position 552 (Leu552Phe). Mutation Phe473Trp led to a total loss of function; mutants Met549Ser and Leu552Phe interfered with the enzyme specificity leading to enhanced friedelin production, in addition to α-amyrin and β-amyrin. Hence, these data showed that methionine 549 and leucine 552 are important residues for the function of this synthase.